Influência da preparação de aresta no processo de furação do ferro fundido cinzento FC300 - Wendler, Evandro Rafael (2023)
The cutting-edge preparation has been the focus of recent studies, providing better results in industrial machining processes. Due to the complexity of obtaining this microgeometry, manufacturers often keep the process for its production secret. This study analyzes the influence of the preparation of the cutting edges of interchangeable inserts used in holders for full drilling of FC300 gray cast iron. An automatic diamond paste brushing process was used to obtain a rounded cutting edge. Controlled experiments were carried out using cutting tools that were only sharpened and others prepared with edge radii of 15, 30, and 50 μm. The experiments were carried out on a Romi Discovery 560 CNC machining center. To characterize the micro geometries, the measurements were taken with a μCMM confocal microscope (Alicona). The type of cutting edge wear was analyzed using a scanning electron microscope (MEV). It was also measured the force and torque, chip temperatures (thermographic camera), diameter, roundness, and roughness of the specimen. The results showed an increase in feed force, torque, and chip temperature as the edge radius increased. Furthermore, the edge preparation process led to a lower incidence of irregularities and strengthened the cutting edge. In addition, the use of larger edge radii had a positive influence on the quality of the holes, resulting in lower roughness values. There was material adhesion on the cutting edge in all tools, but it was lower in tools with greater cutting edge radius.